PENGELOLAAN KESAN MASKULINITAS PADA LAKI-LAKI FEMININ DI KOTA PEKANBARU - Azura, Sayyida; Sari, Genny Gustina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
When a man meets some women in group, it may look normal. However, when the man shows an attitude and behavior that is not naturally done by men in general, such as making a soft, seductive voice or being